Career Self-Efficacy Dan Kesiapan Kerja Pada Mahasiswa Semester Akhir - Rizki Diah Baiti; Sri Muliati Abdullah; Novia Sinta Rochwidowati (UIN Sunan Kalijaga, 2017)
This study aims to determine the relationship between career self-efficacy with the readiness of work in the last semester students. The hypothesis proposed is that there is a positive relationship between career self-efficacy and job readiness. Subjects in this study were last semester students of “X” University Yogyakarta with the whole subject 110. Methods of data collection using the scale of Work Readiness and scale Career Self Efficacy. Results of analysis with product moment correlation test obtained (rxy) of 0.772 (p = 0.000). This shows that there is a positive relationship between career self-efficacy with the readiness of work in the last semester students, so the hypothesis proposed in this research is acceptable. Higher the career self-efficacy followed higher the readiness of work in the final semester students. On the contrary, lower the career self-efficacy followed lower the readiness of work on the last semester students. Coefficient of determination (R2) of 0.60 means that the career self-efficacy variable in this study is able to contribute 60% to the readiness of work to the last semester students. This at once confirms the influence of other variables that are not examined in this study by 40%.